Maternal treatment with fluoxetine promotes testicular alteration in male rat pups - Ramos, Aline Camargo; Santos, Alice Hartmann dos; Silveira, Kennia Moura; Kiss, Ana Carolina Inhasz [UNESP]; Mesquita, Suzana de Fátima Paccola; Gerardin, Daniela Cristina Ceccatto (CSIRO Publishing, 2016)
Fluoxetine (FLX) is a selective serotonin reuptake inhibitor (SSRI) antidepressant commonly prescribed during pregnancy and lactation. Pre- and post-partum depression, as well as SSRI treatment during these periods, may change maternal care, interfering with offspring development. Moreover, it is known that SSRIs may alter testes structure and function in offspring. The present study investigated the effects of maternal FLX exposure on maternal behaviour and testes function in offspring. Female Wistar rats were treated with 7.5 mg kg 1 FLX or tap water (control group) by gavage from the Day 1 of pregnancy until 21 days after birth (postnatal Day (PND) 21). Maternal behaviour was evaluated and morphofunctional analyses of offspring testes were conducted on PND 21 and 50. There were no significant differences between the FLX-treated and control groups regarding maternal behaviour. Nor did maternal treatment with FLX have any effect on bodyweight gain, anogenital distance, day of preputial separation, testis weight and the gonadosomatic index in male offspring. However, there was a decreased number of Sertoli cells at both PND 21 and 50 in FLX-exposed male offspring. The findings of the present study demonstrate that maternal exposure to FLX can impair testicular function in weanling and pubertal animals.
Keywords: Antidepressant; Maternal behaviour; Tests